Financial Analysis of Small Fisherman's Hand Line Fishing Business in Kupang City - Ratung, Agustinus Apriyadi Hanggum; Suharyanto, Suharyanto; Nainggolan, Chandra (Jurnal Kelautan dan Perikanan Terapan (JKPT), 2023)
The development of the capture fisheries business requires every company and fishery business actor, especially small scale fishermen, to compete and increase the catch from each of their business activities. So that the level of business feasibility is a criterion for investment or long-term investment in a particular production. The purpose of this study was to analyze the  handline busines with a vessel size of 2 GT -10 GT in the waters of the city of Kupang. The research method used is a survey method, determining respondents based on purposive sampling. Data collecting done by interview and observation. The data analysis used is descriptive qualitative and quantitative analysis. 30 fishermen who owned handline boats with a size of 2-10 GT were used as the samples. The research was conducted in March - May 2023 at the Tenau Beach Fishing Port (PPP), Kupang city. The business analysis carried out is to look at the average investment costs, fixed costs, operational costs, income and profits of fishing business within 1 year. The results showed that the average investment cost was IDR 161,361,619/year, the total cost was IDR. 354,999,991, -/year total revenue of IDR. 891.066.667.-/year and the ship owner's profit was IDR. 536,066,676,-/year. Based on the results of the analysis, the R/C Ratio and B/C Ratio values are greater than ≥ 1, so it can be concluded that the 2-10 GT small handline fishing vessel business in the waters of Kupang city is profitable and feasible to develop.